Penerapan Keputusan Menteri Kesehatan Republik Indonesia NOMOR 519/MENKES/SK/VI/2008 Tentang Pedoman Penyelenggaraan Pasar Sehat di Pasar-Pasar Tradisional di Kabupaten Kebumen Hasil Renovasi Tahun 2011-2013 - Imam Muhsin Mubarok; Lucky Herawati; Haryono Haryono (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Traditional market is one of public places. Poor condition of market sanitation is potential for di-sease transmission. To prevent the occurence of negatif impacts, between 2011 and 2013, the local government of Kebumen, administered by the Office of Industry, Trade, and Market Mana-gement, has renovated 10 out of the existing 35 traditional markets. Nonetheless, this effort has not yet solved the problem of poor sanitation completely. The purpose of this research was to re-veal in what extent the Guidelines of Market Sanitation, as described by the decree of the Minis-try of Health No.519/2008, had been applied by the government, i.e. by conducting a descriptive study. As the samples were all those 10 traditional markets, and there were three variables that were observed by using a check-list. The variables were: building construction, sanitation, and other facilities. The results showed that, in average, for building construction that consisted of 95 components, 52,9 % had been fulfilled; for sanitation that consisted of 44 components, 47,3 % had been fulfilled, and for other facilities that consisted of 22 componnets, 29,5 % had been fulfilled. Based on the above decree, it can be concludes that 80 % of the renovated traditional markets are categorized as unhealthy, and 20 % are classified as not healthy enough.